Hot-rolled steel sheets and electric resistance welded steel pipes
Patent Information
- Application Number
- JP2024506918
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-02-09
- Filing Date
- 2023-11-17
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2043-11-17
Smart Images

Figure 0007635881000005 
Figure 0007635881000006 
Figure 0007635881000007
Abstract
Description
[Technical field]
[0001] The present invention relates to an electric resistance welded steel pipe suitable for building structures, line pipes, etc., and a hot rolled steel sheet which is a material for the electric resistance welded steel pipe. [Background technology]
[0002] Electric resistance welded steel pipes used in building structures and line pipes suffer a sudden drop in strength and break when buckling occurs when subjected to external forces such as earthquakes. Therefore, it is desirable to suppress the occurrence of buckling in these electric resistance welded steel pipes. In order to suppress buckling of electric resistance welded steel pipes, it is effective to suppress flattening of the steel pipe cross section, which is a precursor phenomenon to buckling.
[0003] There have been few studies conducted to address such requirements. For example, Patent Document 1 discloses a steel pipe in which an electric resistance welded steel pipe as a mother pipe is heated and subjected to hot diameter reduction rolling to set the r-value in the longitudinal direction of the pipe to 1.0 or more, thereby suppressing buckling during bending. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 6954504 [Non-patent literature]
[0005] [Non-Patent Document 1] Hidetoshi Kobayashi, Hiroshi Okubo, Masashi Taimaruya: Light Metals, 39, (1989), p.8 Summary of the Invention [Problem to be solved by the invention]
[0006] As in Patent Document 1, it is possible to suppress flattening of the steel pipe cross section by increasing the r-value in the axial direction of the steel pipe, promoting the deformation in the circumferential direction of the pipe and reducing the change in wall thickness. However, this causes the diameter of the steel pipe cross section to shrink, causing necking and reducing the cross-sectional area, which reduces the strength of the structure.
[0007] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide an electric resistance welded steel pipe having excellent flattening resistance, and a hot rolled steel sheet to be used as a raw material for the electric resistance welded steel pipe.
[0008] In the present invention, "excellent flattening resistance" means that no cracks of 0.50 mm or more in length occur until the inner surfaces of flattened test pieces taken from an electric resistance welded steel pipe come into contact with each other in a flattening test, and (normalized load / normalized displacement calculated by the following formula (1)) is 100 MPa or more when the normalized displacement calculated by formula (2) is in the range of 0.20 to 0.30. The fact that the inner surfaces of the flattened test pieces taken from the electric resistance welded steel pipe come into contact with each other means, for example, that when a flattening test is performed by applying loads from above and below the flattened test piece taken from the electric resistance welded steel pipe, the inner surfaces of the upper and lower parts of the flattened test piece taken from the electric resistance welded steel pipe come into contact with each other. (Normalized load (MPa))=(P / L)×(r / t 2 )×(1-((x0-x) / 2r) 2 ) 1 / 2 (1) (Normalized displacement) = (x0-x) / 2r (2) Where: P: Load (N) L: Initial length of the flattened test piece in the axial direction (mm) r: Initial radius of curvature of the outer surface of the bent flattened test piece (mm) t: initial thickness of flattened test piece (mm) x0: initial distance between two plates (mm) x: Distance between two plates (mm) [Means for solving the problem]
[0009] As a result of intensive research, the inventors have found that by increasing the proportion of fine grains in the microstructure of an electric resistance welded steel pipe, toughness can be improved and the occurrence of cracks in a flattening test can be suppressed. On the other hand, they have also found that if the proportion of fine grains becomes too high, ductility decreases and cracks are more likely to occur before adhesion in a flattening test.
[0010] In addition, it was found that by increasing the connectivity of fine grains, the increase in load relative to the displacement (indentation amount) in the flattening test can be increased, and the resistance to flattening can be increased. On the other hand, it was also found that if the connectivity of fine grains becomes too high, the ductility decreases, and cracks occur before adhesion in the flattening test.
[0011] Furthermore, it was found that electric resistance welded steel pipes manufactured from hot rolled steel sheets, which have a high resistance to flattening in a C-type flattening test, have excellent flattening resistance.
[0012] The present invention has been completed based on the above findings, and provides the following [1] to [6]. [1] The test is performed by bending a steel plate into a U-shape and clamping it between two flat plates. In the C-type flattening test, No cracks of 0.50 mm or more in length are generated until the inner surfaces of the bent test pieces come into contact with each other, and A hot-rolled steel sheet in which the normalized load / normalized displacement calculated by the following formula (1) is 100 MPa or more, when the normalized displacement calculated by the following formula (2) is in the range of 0.20 to 0.30. (Normalized load (MPa))=(P / L)×(r / t 2 )×(1-((x0-x) / 2r) 2 ) 1 / 2 (1) (Normalized displacement) = (x0-x) / 2r (2) Where: P: Load (N) L: Initial length of the flattened test piece (mm) r: Initial radius of curvature of the outer surface of the bent flattened test piece (mm) t: initial thickness of flattened test piece (mm) x0: initial distance between two plates (mm) x: Distance between two plates (mm) [2] The composition is in mass percent: C: 0.020% or more and 0.200% or less, Si: 0.50% or less, Mn: 0.30% or more and 2.00% or less, P: 0.050% or less, S: 0.0200% or less, Al: 0.005% or more and 0.100% or less, N: Contains 0.0100% or less, Or even more so: Nb: 0.080% or less, V: 0.080% or less, Ti: 0.080% or less, Cu: 0.50% or less, Ni: 0.50% or less, Cr: 0.50% or less, Mo: 0.50% or less Ca: 0.0050% or less, B: 0.0050% or less, Mg: 0.020% or less, Zr: 0.020% or less, REM: 0.020% or less, Sn: Contains one or more of the following: 0.100% or less; The balance consists of Fe and unavoidable impurities. [1] The hot-rolled steel sheet according to the present invention. [3] The steel structure at the center of the plate thickness is The average grain size of the grains in the region surrounded by the high-angle grain boundaries is 15.0 μm or less, The crystal grains having a grain size equal to or smaller than the average crystal grain size are 10% or more and 50% or less in terms of area ratio with respect to all crystal grains, The fine grain connectivity calculated by the following formula (3) is 0.05 or more and 0.50 or less, and Bainite is 10% or more by volume, The total volume fraction of ferrite and bainite is 80% or more, The balance is one or more selected from pearlite, martensite, and austenite, the total of which is 20% or less by volume. The hot-rolled steel sheet according to [1] or [2]. (Fine grain connectivity) = (Total length of high angle boundaries in grains with grain sizes smaller than the average grain size) / (Total length of high angle boundaries) (3) However, the numerator on the right side of equation (3) does not include the length of the high-angle grain boundaries between crystal grains smaller than the average crystal grain size and crystal grains larger than the average crystal grain size. [4] An electric resistance welded steel pipe having a base metal portion and an electric resistance welded portion, In a flattening test, a flattened test piece taken from an electric resistance welded steel pipe is clamped between two flat plates. No cracks of 0.50 mm or more in length are generated until the inner surfaces of the flattened test pieces come into contact with each other, and An electric resistance welded steel pipe in which the normalized load / normalized displacement calculated by the following formula (1) is 100 MPa or more when the normalized displacement calculated by the following formula (2) is in the range of 0.20 to 0.30. (Normalized load (MPa))=(P / L)×(r / t 2 )×(1-((x0-x) / 2r) 2 ) 1 / 2 (1) (Normalized displacement) = (x0-x) / 2r (2) Where: P: Load (N) L: Initial length of the flattened test piece in the axial direction (mm) r: Initial radius of curvature of the outer surface of the bent flattened test piece (mm) t: initial thickness of flattened test piece (mm) x0: initial distance between two plates (mm) x: Distance between two plates (mm) [5] The composition of the base material is, in mass%, C: 0.020% or more and 0.200% or less, Si: 0.50% or less, Mn: 0.30% or more and 2.00% or less, P: 0.050% or less, S: 0.0200% or less, Al: 0.005% or more and 0.100% or less, N: 0.0100% or less, Or even more so: Nb: 0.080% or less, V: 0.080% or less, Ti: 0.080% or less, Cu: 0.50% or less, Ni: 0.50% or less, Cr: 0.50% or less, Mo: 0.50% or less Ca: 0.0050% or less, B: 0.0050% or less, Mg: 0.020% or less, Zr: 0.020% or less, REM: 0.020% or less, Sn: Contains one or more of the following: 0.100% or less; The balance consists of Fe and unavoidable impurities. [4] The electric resistance welded steel pipe according to the present invention. [6] The steel structure at the center of the thickness of the base material is The average grain size of the grains in the region surrounded by the high-angle grain boundaries is 15.0 μm or less, The crystal grains having a grain size equal to or smaller than the average crystal grain size are 10% or more and 50% or less in terms of area ratio with respect to all crystal grains, The fine grain connectivity calculated by the following formula (3) is 0.05 or more and 0.50 or less, and Bainite is 10% or more by volume, The total volume fraction of ferrite and bainite is 80% or more, The balance is one or more selected from pearlite, martensite, and austenite, the total of which is 20% or less by volume. [4] or [5]. (Fine grain connectivity) = (Total length of high angle boundaries in grains with grain sizes smaller than the average grain size) / (Total length of high angle boundaries) (3) However, the numerator on the right side of equation (3) does not include the length of the high-angle grain boundaries between crystal grains smaller than the average crystal grain size and crystal grains larger than the average crystal grain size. Effect of the Invention
[0013] According to the present invention, it is possible to provide an electric resistance welded steel pipe having excellent flattening resistance, and a hot rolled steel sheet used as a raw material for the electric resistance welded steel pipe. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 is a schematic diagram showing the relationship between standardized load and standardized displacement in a flattening test. [Figure 2(a)] This is a diagram showing the sampling direction of a C-shaped flattened test piece of a hot-rolled steel sheet, observed from the side. [Figure 2(b)] This is a side view of the flattening test of a C-shaped flattened test piece of hot-rolled steel sheet. [Diagram 3] This is a side view of the flattening test of an electric resistance welded steel pipe. [Figure 4] 1 is a schematic diagram of a circumferential cross section of an electric resistance welded portion of an electric resistance welded steel pipe. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The hot-rolled steel sheet and electric resistance welded steel pipe, as well as the manufacturing methods thereof, of the present invention will be described below.
[0016] First, the reasons for limiting the mechanical properties of the hot-rolled steel sheet and electric resistance welded steel pipe of the present invention will be explained.
[0017] The hot-rolled steel sheet of the present invention is characterized in that in a C-type flattening test, no cracks with a length of 0.50 mm or more occur until the inner surfaces of the bent steel sheets come into contact with each other in a tight fit, and the value of normalized load / normalized displacement in the normalized displacement range of 0.20 to 0.30 is 100 MPa or more. The electric welded steel pipe of the present invention is also characterized in that, in a flattening test, no cracks occur until the inner surfaces of flattened test pieces taken from the electric welded steel pipe come into contact with each other in a tight adhesion state, and the value of normalized load / normalized displacement in the normalized displacement range of 0.20 to 0.30 is 100 MPa or more. The normalized load and normalized displacement are calculated using equations (1) and (2), respectively. (Normalized load (MPa))=(P / L)×(r / t 2 )×(1-((x0-x) / 2r) 2 ) 1 / 2 (1) (Normalized displacement) = (x0-x) / 2r (2) Where: P: Load (N) L: Initial length of the flattened test piece (mm) r: Initial radius of curvature of the outer surface of the bent flattened test piece (mm) t: initial thickness of flattened test piece (mm) x0: initial distance between two plates (mm) x: Distance between two plates (mm) Furthermore, the value of normalized load / normalized displacement when the normalized displacement is in the range of 0.20 to 0.30 is calculated by ((normalized load when the normalized displacement is 0.30)-(normalized load when the normalized displacement is 0.20)) / (0.30-0.20).
[0018] In addition, the phrase "no cracks occur until the flattening test is in a tight contact state" refers to the fact that no cracks occur until the inner surfaces of the flattened test pieces taken from the electric resistance welded steel pipe come into contact with each other, and the phrase "the inner surfaces of the flattened test pieces taken from the electric resistance welded steel pipe come into contact with each other" refers to the fact that, for example, when a flattening test is performed by applying a load from above and below the flattened test pieces taken from the electric resistance welded steel pipe, the inner surfaces of the upper and lower parts of the flattened test pieces taken from the electric resistance welded steel pipe come into contact with each other. The above-mentioned cracks refer to cracks of a size that can be visually confirmed. The size that can be visually confirmed is a length of 0.50 mm or more. There is no particular upper limit to the length of the crack, but since the crack is linear, it is preferable to target a length equal to or less than the length of the test piece in the tube axis direction. In addition, the length refers to the longitudinal size of the crack.
[0019] In the C-type flattening test and flattening test, the greater the increase in load relative to the distance (indentation) between the two plates, the greater the resistance to flattening. However, even if the material is the same, the load and displacement change depending on the dimensions and shape of the test piece. Therefore, as described in Non-Patent Document 1, the load and displacement are standardized by equations (1) and (2), respectively.
[0020] In the C-type flattening test and the flattening test, the test piece undergoes elastic deformation until the normalized displacement reaches a certain value, after which the test piece yields and plastic deformation also occurs. Figure 1 shows a schematic diagram of the relationship between normalized load and normalized displacement in the flattening test. In the curve 1 showing the change in normalized load with normalized displacement shown in Figure 1, in the elastic region 2 until the test piece yields, as shown in Figure 1, the normalized load and the normalized displacement are in a proportional relationship. After that, when the test piece yields and enters the plastic region 3, the slope of the curve (normalized load / normalized displacement) becomes smaller, and the test proceeds while maintaining a constant slope. After that, the test proceeds while the slope of the curve (normalized load / normalized displacement) shows a higher value than the slope (slope after entering the plastic region 3), and the test ends when cracks occur on the outer bent surface or when the inner surfaces of the test pieces come into contact with each other (the inner surfaces of the upper and lower parts come into contact) and come into close contact. Hereafter, the state of the test piece at the end of the test is also referred to as the cracked or adhered state4.
[0021] If cracks occur before the bonded state is reached, a sudden drop in load will occur. Therefore, in the present invention, it is important to prevent cracks from occurring until the bonded state is reached in order to ensure the safety of the structure.
[0022] In the present invention, (normalized load / normalized displacement) in the plastic region 3 is used as an index of flattening resistance. That is, the larger the (normalized load / normalized displacement), the higher the resistance to flattening and the higher the flattening resistance. In the present invention, the (normalized load / normalized displacement) is set to 100 MPa or more in the range of 0.20 to 0.30, which corresponds to the first half of the plastic region 3. Preferably, the (normalized load / normalized displacement) is 120 MPa or more. More preferably, the (normalized load / normalized displacement) is 140 MPa or more. Even more preferably, the (normalized load / normalized displacement) is 150 MPa or more. However, if the (normalized load / normalized displacement) exceeds 600 MPa, the ductility decreases, and cracks are likely to occur before the adhesion state is reached. Therefore, the value of the (normalized load / normalized displacement) is preferably 600 MPa or less. More preferably, the (normalized load / normalized displacement) is 550 MPa or less. More preferably, the value of (normalized load / normalized displacement) is 500 MPa or less. Most preferably, the value of (normalized load / normalized displacement) is 450 MPa or less.
[0023] The reason why the range of the normalized displacement is set to 0.20 to 0.30 is that the value of (normalized load / normalized displacement) becomes almost constant and stable in the plastic region.
[0024] The C-type flattening test refers to a test in which a test piece made by bending a single steel plate into a U-shape is clamped between two flat plates.
[0025] In the C-type flattening test, a plate material with a width of 50 mm x t (t: plate thickness) and a length of 100 mm is taken from a hot-rolled steel plate so that the longitudinal direction of the test piece is the plate width direction of the hot-rolled steel plate, and then this is made into a C-type test piece by the press-bending method described in JIS Z 2248 (2006), and then the test is performed according to the method described in JIS G 3441 (2021). Figure 2 (a) shows a diagram of the hot-rolled steel plate C-type flattened test piece taken in the direction and the state after it was made into a C-type flattened test piece observed from the side. The test piece before being made into a C-type flattened test piece is designated by the symbol 5A, and the C-type flattened test piece after being made into a C-type flattened test piece is designated by the symbol 5. The initial length and initial thickness do not change before and after being made into a C-type flattened test piece. The initial length 100 of the C-shaped flattened test piece (flattened test piece) 5 refers to the above-mentioned length of 50 mm, and the length direction of the C-shaped flattened test piece 5 is the rolling direction 102 of the hot-rolled steel sheet. The initial thickness of the C-shaped flattened test piece (flattened test piece) 5 is denoted by the symbol 101. Figure 2(b) shows a diagram of the state of the flattening test of the C-shaped flattened test piece of the hot-rolled steel sheet observed from the side. The C-shaped flattening test is a test method in which, as shown in Figures 2(a) and 2(b), a single cut-out test piece 5A is bent into a U-shape to form a C-shaped flattened test piece 5, and the C-shaped flattened test piece 5 is sandwiched between two flat plates 6, and a load is applied in the compression direction 7 perpendicular to the flat plates 6 while testing until the above-mentioned state is reached. In the press bending of the C-shaped flattened test piece 5, the inner radius of the tip of the press fitting is 9 x t (mm). The initial radius of curvature r (mm) of the outer bent surface of the C-shaped flattened test piece is calculated by adding the plate thickness t (mm) to the inner radius of the tip of the pressing metal fitting in the above pressing, as shown in formula (4). r = 10 × t (4) The flattening test is performed by taking a test piece cut into a ring with a length of 100 mm in the axial direction from an electric-resistance welded steel pipe including an electric-resistance weld, from the axial direction of the pipe, and following the method described in JIS G 3441 (2021). However, the flattening test piece 8 is placed so that the line connecting the electric-resistance welded part 9 and the center 10 of the electric-resistance welded steel pipe faces in a direction parallel to the compression direction 12, as shown in Figure 3. The initial radius of curvature r of the outer surface of the bent flattening test piece 8 is 1 / 2 the outer diameter of the electric-resistance welded steel pipe.
[0026] The composition of the base material of the hot-rolled steel sheet and electric resistance welded steel pipe of the present invention is, in mass%, C: 0.020% or more and 0.200% or less, Si: 0.50% or less, Mn: 0.30% or more and 2.00% or less, P: 0.050% or less, S: 0.0200% or less, Al: 0.005% or more and 0.100% or less, N: Contains 0.0100% or less, Or even more so: Nb: 0.080% or less, V: 0.080% or less, Ti: 0.080% or less, Cu: 0.50% or less, Ni: 0.50% or less, Cr: 0.50% or less, Mo: 0.50% or less Ca: 0.0050% or less, B: 0.0050% or less, Mg: 0.020% or less, Zr: 0.020% or less, REM: 0.020% or less, Sn: Contains one or more of the following: 0.100% or less; The balance preferably consists of Fe and unavoidable impurities.
[0027] In this specification, unless otherwise specified, "%" indicating a steel composition is "mass %".
[0028] C: 0.020% or more and 0.200% or less C is an element that increases the strength of steel by solid solution strengthening. In addition, C improves the hardenability of steel, thereby increasing the proportion of fine grains, improving toughness, and contributing to suppressing the occurrence of cracks in a flattening test, and also contributes to increasing the resistance to flattening by increasing the degree of connectivity of fine grains. In order to obtain such effects, it is preferable to contain 0.020% or more of C. More preferably, the C content is 0.025% or more, and even more preferably, 0.030% or more. Most preferably, the C content is 0.035% or more. However, if the C content exceeds 0.200%, hard pearlite, martensite, and austenite are excessively generated, ductility is reduced, and cracks are likely to occur before the steel is in a tight contact state in a C-type flattening test or a flattening test. Therefore, the C content is preferably 0.200% or less. The C content is more preferably 0.180% or less. Even more preferably, it is 0.170% or less. Most preferably, the C content is equal to or less than 0.165%.
[0029] Si:0.50% or less Silicon is an element that increases the strength of steel by solid solution strengthening. In order to obtain such an effect, it is preferable that the steel contains 0.02% or more of silicon. The silicon content is more preferably 0.05% or more, and even more preferably 0.08% or more. The silicon content is most preferably 0.10% or more. However, if the silicon content exceeds 0.50%, the ductility decreases, and cracks tend to occur before the steel reaches a tightly adhered state in the flattening test. Therefore, the silicon content is preferably 0.50% or less. The silicon content is more preferably 0.40% or less. Even more preferably 0.30% or less. The silicon content is most preferably 0.28% or less.
[0030] Mn: 0.30% or more and 2.00% or less Mn is an element that increases the strength of steel by solid solution strengthening. In addition, Mn improves the hardenability of steel, thereby increasing the proportion of fine grains, improving toughness, and contributing to suppressing the occurrence of cracks in a flattening test, and also contributes to increasing the resistance to flattening by increasing the connectivity of fine grains. In order to obtain such effects, it is preferable to contain 0.30% or more of Mn. The Mn content is more preferably 0.40% or more, and even more preferably 0.50% or more. The Mn content is most preferably 0.60% or more. However, if the Mn content exceeds 2.00%, hard pearlite, martensite, and austenite are excessively generated, ductility is reduced, and cracks are likely to occur before the flattening test is in a tight contact state. Therefore, the Mn content is preferably 2.00% or less. The Mn content is more preferably 1.90% or less. Even more preferably 1.80% or less. The Mn content is most preferably 1.75% or less.
[0031] P:0.050% or less Since P segregates at grain boundaries and reduces toughness, it is preferable to reduce it as an inevitable impurity as much as possible, and the P content is preferably in the range of 0.050% or less. The P content is more preferably 0.040% or less, and further preferably 0.030% or less. The P content is most preferably 0.020% or less. Although there is no particular lower limit for P, since excessive reduction leads to an increase in smelting costs, it is preferable that P is 0.001% or more.
[0032] S: 0.0200% or less S is usually present in steel as MnS, but MnS is thinly drawn in the hot rolling process and has a negative effect on ductility and toughness. For this reason, in the present invention, it is preferable to reduce S as much as possible, and the S content is preferably 0.0200% or less. The S content is more preferably 0.0100% or less, and further preferably 0.0050% or less. The S content is most preferably 0.0030% or less. Although there is no particular lower limit for S, since excessive reduction leads to an increase in smelting costs, it is preferable that S is 0.0001% or more.
[0033] Al: 0.005% or more and 0.100% or less Al is an element that acts as a strong deoxidizer. In order to obtain such an effect, it is preferable that the Al content is 0.005% or more. The Al content is more preferably 0.010% or more, and even more preferably 0.015% or more. The Al content is most preferably 0.020% or more. However, if the Al content exceeds 0.100%, the weldability deteriorates, and the amount of alumina-based inclusions increases, resulting in deterioration of the surface properties. For this reason, the Al content is preferably 0.100% or less. The Al content is more preferably 0.080% or less. Even more preferably 0.070% or less. The Al content is most preferably 0.065% or less.
[0034] N: 0.0100% or less N is an inevitable impurity, and is an element that has the effect of reducing ductility and toughness by firmly fixing the movement of dislocations. In the present invention, it is desirable to reduce N as an impurity as much as possible, but the N content can be tolerated up to 0.0100%. For this reason, the N content is 0.0100% or less. The N content is preferably 0.0080% or less. The N content is more preferably 0.0070% or less. The N content is further preferably 0.0065% or less. The N content is most preferably 0.0060% or less. The lower limit is not particularly limited, but since excessive reduction leads to an increase in refining costs, it is preferable to set it to 0.0010% or more.
[0035] In addition to the above-mentioned chemical composition, the electric welded steel pipe and the hot rolled steel sheet of the present invention may further contain one or more of Nb, V, Ti, Cu, Ni, Cr, Mo, Ca, B, Mg, Zr, REM, and Sn.
[0036] Nb: 0.080% or less Nb is an element that contributes to improving the strength of steel by forming fine carbides and nitrides in the steel, and also contributes to refining the structure by suppressing the coarsening of austenite during hot rolling, and can be contained as necessary. In order to obtain the above-mentioned effects, when Nb is contained, it is preferable that 0.002% or more of Nb is contained. More preferably, the Nb content is 0.005% or more, and even more preferably, 0.010% or more. The Nb content is most preferably 0.012% or more. However, when the Nb content exceeds 0.080%, the ductility and toughness decrease. Therefore, when Nb is contained, the Nb content is 0.080% or less. More preferably, the Nb content is 0.070% or less. Even more preferably, the Nb content is 0.065% or less. The Nb content is most preferably 0.060% or less.
[0037] V:0.080% or less V is an element that contributes to improving the strength of steel by forming fine carbides and nitrides in the steel, and can be contained as necessary. In order to obtain the above-mentioned effects, when V is contained, it is preferable that V is contained in an amount of 0.002% or more. More preferably, the V content is 0.005% or more, and even more preferably, 0.010% or more. The V content is most preferably 0.015% or more. However, when the V content exceeds 0.080%, the ductility and toughness decrease. Therefore, when V is contained, the V content is 0.080% or less. More preferably, it is 0.070% or less. Even more preferably, it is 0.065% or less. The V content is most preferably 0.060% or less.
[0038] Ti: 0.080% or less Ti is an element that contributes to improving the strength of steel by forming fine carbides and nitrides in steel, and also contributes to reducing the amount of dissolved N in steel due to its high affinity with N, and can be contained as necessary. In order to obtain the above-mentioned effects, when Ti is contained, it is preferable that Ti is contained in an amount of 0.002% or more. More preferably, the Ti content is 0.005% or more, and even more preferably, 0.010% or more. The Ti content is most preferably 0.012% or more. However, if the Ti content exceeds 0.080%, the ductility and toughness decrease. Therefore, when Ti is contained, the Ti content is 0.080% or less. More preferably, the Ti content is 0.070% or less. Even more preferably, the Ti content is 0.065% or less. The Ti content is most preferably 0.060% or less.
[0039] Cu: 0.50% or less, Ni: 0.50% or less Cu and Ni are elements that increase the strength of steel by solid solution strengthening, and also contribute to improving the hardenability of steel and refining the structure, and can be contained as necessary. In order to obtain the above-mentioned effects, when Cu is contained, the Cu content is preferably 0.01% or more. More preferably, it is 0.05% or more. Even more preferably, it is 0.10% or more. In order to obtain the above-mentioned effects, when Ni is contained, the Ni content is preferably 0.01% or more. More preferably, it is 0.05% or more. Even more preferably, it is 0.10% or more. On the other hand, excessive inclusion may cause a decrease in ductility and toughness. In addition, it may cause excessive generation of hard pearlite, martensite, and austenite. Therefore, when Cu is contained, the Cu content is 0.50% or less. Preferably, it is 0.40% or less. More preferably, it is 0.30% or less. In addition, when Ni is contained, the Ni content is 0.50% or less. Preferably, it is 0.40% or less. More preferably, it is 0.30% or less.
[0040] Cr: 0.50% or less, Mo: 0.50% or less Cr and Mo are elements that improve the hardenability of steel and contribute to refining the structure, and can be contained as necessary. In order to obtain the above-mentioned effects, when Cr is contained, the Cr content is preferably 0.01% or more. More preferably, it is 0.05% or more. Even more preferably, it is 0.10% or more. In addition, in order to obtain the above-mentioned effects, when Mo is contained, the Mo content is preferably 0.01% or more. More preferably, it is 0.05% or more. Even more preferably, it is 0.10% or more. On the other hand, excessive inclusion of Cr may lead to excessive formation of hard pearlite, martensite, and austenite. Therefore, when Cr is contained, the Cr content is set to 0.50% or less. Preferably, it is set to 0.40% or less. More preferably, it is set to 0.30% or less. When Mo is contained, the Mo content is set to 0.50% or less. Preferably, it is set to 0.40% or less. More preferably, it is set to 0.30% or less.
[0041] Ca:0.0050% or less Ca is an element that contributes to improving the toughness of steel by spheroidizing sulfides such as MnS that are thinly drawn in the hot rolling process, and can be contained as necessary. In order to obtain the above-mentioned effects, when Ca is contained, it is preferable that Ca is contained in an amount of 0.0005% or more. More preferably, the Ca content is 0.0008% or more, and even more preferably, 0.0010% or more. The Ca content is most preferably 0.0015% or more. However, when the Ca content exceeds 0.0050%, Ca oxide clusters are formed in the steel, and the toughness deteriorates. Therefore, when Ca is contained, the Ca content is 0.0050% or less. Preferably, the Ca content is 0.0040% or less. More preferably, the Ca content is 0.0035% or less. The Ca content is even more preferably 0.0030% or less.
[0042] B: 0.0050% or less B is an element that contributes to the refinement of the structure by lowering the transformation start temperature, and can be contained as necessary. In order to obtain the above-mentioned effects, when B is contained, it is preferable to contain 0.0002% or more of B. More preferably, the B content is 0.0005% or more, and even more preferably, 0.0008% or more. The B content is most preferably 0.0010% or more. However, if the B content exceeds 0.0050%, the ductility and toughness deteriorate. Therefore, when B is contained, the B content is 0.0050% or less. More preferably, it is 0.0040% or less. Even more preferably, it is 0.0030% or less. The B content is most preferably 0.0025% or less.
[0043] Mg: 0.020% or less, Zr: 0.020% or less, REM: 0.020% or less Mg, Zr, and REM are elements that increase the strength of steel through grain refinement, and may be contained as necessary. The Mg content may be 0%, but when Mg is contained, the preferred lower limit is 0.0005% or more. The Mg content is more preferably 0.0008% or more. The Zr content may be 0%, but when Zr is contained, the preferred lower limit is 0.0005% or more. The Zr content is more preferably 0.0008% or more. The REM content may be 0%, but when REM is contained, the preferred lower limit is 0.0005% or more. The REM content is more preferably 0.0008% or more. On the other hand, excessive inclusion may cause an increase in the yield ratio and an increase in the logarithmic standard deviation of the equivalent plastic strain distribution. Therefore, when Mg is contained, the Mg content is set to 0.020% or less. The Mg content is preferably 0.010% or less. When Zr is contained, the Zr content is 0.020% or less. The Zr content is preferably 0.010% or less. When REM is contained, the REM content is 0.020% or less. The REM content is preferably 0.010% or less. Here, REM is a general term for 17 elements in total, including Sc, Y, and lanthanoid elements. One or more of these 17 elements can be contained in the steel, and the REM content means the total content of these elements.
[0044] Sn: 0.100% or less Sn is an element that suppresses decarburization caused by nitriding or oxidation of the steel sheet surface and suppresses the decrease in strength. In order to obtain the above-mentioned effects, it is preferable that the Sn content is 0.001% or more. The Sn content is more preferably 0.002% or more, and even more preferably 0.005% or more. However, if it is contained excessively, the ductility and toughness of the steel are reduced. Therefore, the Sn content is preferably 0.100% or less. The Sn content is more preferably 0.070% or less. The Sn content is even more preferably 0.040% or less.
[0045] The balance is Fe and inevitable impurities. Inevitable impurities are impurities that are inevitably mixed in from raw materials, manufacturing processes, manufacturing equipment, etc., and are allowed to be included to the extent that they do not impair the object of the present invention. Examples of the inevitable impurities in the balance include As, Sb, Bi, Co, Pb, Zn, O, Ta, W, Te, Hf, Ge, Sr, and Cs. Examples of raw materials for the steel sheet include iron ore, reduced iron, and scrap.
[0046] It is preferable that the steel structure at the center of thickness of the hot-rolled steel plate of the present invention and the center of thickness of the base material of the electric-resistance welded steel pipe has an average grain size of 15.0 μm or less, which is the region surrounded by high-angle grain boundaries, and grains having a grain size less than the average grain size account for 10% or more and 50% or less in area ratio of all grains, the fine grain connectivity calculated by the following formula (3) is 0.05 or more and 0.50 or less, and furthermore, bainite accounts for 10% or more in volume fraction, the total of ferrite and bainite accounts for 80% or more in volume fraction, and the remainder is one or more types selected from pearlite, martensite and austenite in total account for 20% or less in volume fraction.
[0047] (Fine grain connectivity) = (Total length of high angle boundaries in grains with grain sizes smaller than the average grain size) / (Total length of high angle boundaries) (3) However, the numerator on the right side of equation (3) does not include the length of the high-angle grain boundaries between crystal grains smaller than the average crystal grain size and crystal grains larger than the average crystal grain size.
[0048] The average grain size, the area ratio of grains with a grain size equal to or smaller than the average grain size, and the degree of fine grain connectivity are measured using the SEM / EBSD method. The measurement area is 500 μm × 500 μm, the measurement step size is 0.5 μm, and the measured values of 5 or more fields are averaged. Based on the obtained EBSD data, the crystal orientation analysis software OIM Analysis (trademark) is used to obtain the distribution of grain boundaries and grain size, with boundaries with an orientation difference of 15° or more being regarded as grain boundaries (high-angle grain boundaries). The average grain size is calculated as the diameter (equivalent circle diameter) of a circle with an area equal to the value obtained by dividing the total measured area by the number of grains. The degree of fine grain connectivity is calculated by calculating the total length of the high-angle grain boundaries in the area excluding the grains with a grain size equal to or larger than the average grain size (i.e., only the grains with a grain size smaller than the average grain size), and the total length of all the high-angle grain boundaries, and then calculating the ratio between them. However, high-angle boundaries in regions excluding grains with grain sizes equal to or larger than the average grain size do not include high-angle boundaries between grains smaller than the average grain size and grains with grain sizes equal to or larger than the average grain size.In calculating the average grain size, the area ratio of grains with grain sizes equal to or smaller than the average grain size, and the fine grain connectivity, grains with grain sizes of 1.0 μm or less are excluded as measurement noise.
[0049] When the average crystal grain size is large, the toughness decreases and cracks are more likely to occur in the flattening test. In addition, the value of (normalized load / normalized displacement) may also decrease. Therefore, the average crystal grain size is preferably 15.0 μm or less. The average crystal grain size is more preferably 12.0 μm or less. Further preferably, it is 10.0 μm or less. The average crystal grain size is most preferably 9.0 μm or less. Note that, when the average crystal grain size is small, the ductility decreases and cracks are more likely to occur in the flattening test, so the average crystal grain size is preferably 2.0 μm or more. More preferably, it is 3.0 μm or more. Further preferably, the average crystal grain size is 3.5 μm or more.
[0050] When the area ratio of crystal grains having a grain size equal to or smaller than the average grain size is low, the degree of connectivity of fine grains equal to or smaller than the average grain size is low, and the resistance to flattening may be low. In addition, the toughness is reduced, and cracks are more likely to occur in the flattening test. Therefore, the above area ratio is preferably 10% or more. The above area ratio is more preferably 12% or more. Even more preferably 15% or more. When the above area ratio exceeds 50%, the degree of connectivity of fine grains is high, ductility is reduced, and cracks are more likely to occur in the flattening test. Therefore, the above area ratio is preferably 50% or less. The above area ratio is more preferably 45% or less. Even more preferably 40% or less. The above area ratio is most preferably 35% or less.
[0051] When the degree of fine grain connectivity is low, the degree of connectivity between coarse grains is high, and strains in the coarse grains are easily connected to each other. Since the coarse grains are soft and relatively large strains occur within the grains, when they are connected, stress concentration occurs and resistance to flattening may be reduced. Therefore, the degree of fine grain connectivity is preferably 0.05 or more. More preferably, it is 0.10 or more. The degree of fine grain connectivity is further preferably 0.11 or more. The degree of fine grain connectivity is most preferably 0.12 or more. When the degree of fine grain connectivity is high, the hard fine grains act as a parent phase, so the ductility decreases and cracks are more likely to occur in the flattening test. Therefore, the degree of fine grain connectivity is preferably 0.50 or less. The degree of fine grain connectivity is more preferably 0.47 or less. Even more preferably, it is 0.40 or less. The degree of fine grain connectivity is most preferably 0.35 or less.
[0052] Ferrite is a soft structure. Bainite is harder than ferrite and softer than pearlite, martensite, and austenite, so controlling the structure of bainite is important from the viewpoints of strength, ductility, and toughness.
[0053] When the volume fraction of bainite is small, the proportion of soft ferrite increases, and strength decreases. Also, the value of (normalized load / normalized displacement) may decrease. Therefore, the volume fraction of bainite is preferably 10% or more. The volume fraction of bainite is more preferably 12% or more. Further, it is more preferably 20% or more. Most preferably, the volume fraction of bainite is 25% or more. There is no particular upper limit, but it is preferably 75% or less because ductility decreases.
[0054] When the total volume fraction of ferrite and bainite is small, the ratio of hard pearlite, martensite and austenite increases, and ductility and toughness decrease. Therefore, the total volume fraction of ferrite and bainite is preferably 80% or more, more preferably 85% or more, and further preferably 88% or more. For the above reasons, the total volume fraction of hard pearlite, martensite and austenite is preferably 20% or less. On the other hand, if the total of hard pearlite, martensite and austenite is less than 1%, ductility decreases, so the total of ferrite and bainite is preferably 99% or less in volume fraction, more preferably 98% or less, and even more preferably 97% or less.
[0055] The above-mentioned various structures except for austenite have nucleation sites at austenite grain boundaries or deformation bands within austenite grains. In hot rolling, by increasing the reduction at low temperatures where austenite recrystallization is difficult to occur, a large number of dislocations can be introduced into the austenite to refine the austenite and a large number of deformation bands can be introduced into the grains. This increases the area of the nucleation sites, increases the frequency of nucleation, and refines the steel structure.
[0056] Here, the observation of the steel structure can be performed by the method described below. First, a test piece for structure observation is taken so that the observation surface is a cross section parallel to both the rolling direction and the thickness direction and the thickness center of a hot-rolled steel sheet, and a cross section parallel to both the axial direction and the thickness direction and the thickness center of an electric resistance welded steel pipe, and is prepared by polishing and etching with nital. For the structure observation, an optical microscope (magnification: 1000 times) or a scanning electron microscope (SEM, magnification: 1000 times) is used to observe and photograph the structure in the thickness (or thickness) center. Next, the area ratio of bainite and the remainder (ferrite, pearlite, martensite, austenite) is obtained from the obtained optical microscope image and SEM image. The area ratio of each structure is calculated as the average value of the values obtained in five or more visual fields by observing the structure. In the present invention, the area ratio obtained by the structure observation is the volume ratio of each structure. The judgment of whether or not it is each structure is performed according to the following contents.
[0057] Ferrite is a product of diffusion transformation, and has a low dislocation density and a nearly restored structure. This includes polygonal ferrite and pseudo-polygonal ferrite. Areas where no cementite is observed with an optical microscope or SEM, and where the lath structure, which is the substructure, is not observed, are judged to be ferrite.
[0058] Bainite is a complex phase structure of lath-shaped ferrite and cementite with high dislocation density. Areas where cementite is dispersed or where a lath structure, which is a substructure, is observed using an optical microscope or SEM are judged to be bainite.
[0059] Pearlite is a eutectoid structure of iron and iron carbide (ferrite + cementite), and exhibits a lamellar structure in which linear ferrite and cementite are arranged alternately. The area observed as above with SEM is determined to be pearlite.
[0060] Martensite is a lath-shaped low-temperature transformed structure with an extremely high dislocation density. In SEM images, it shows brighter contrast than ferrite and bainite.
[0061] Since it is difficult to distinguish between martensite and austenite in optical microscope images and SEM images, the area fraction of the structure observed as martensite or austenite in the obtained SEM image is measured, and the volume fraction of austenite measured by the method described below is subtracted from the measured value to determine the volume fraction of martensite.
[0062] Austenite is an fcc phase, and the volume fraction of austenite is measured by X-ray diffraction using a test piece prepared in the same way as the test piece used to measure dislocation density. The volume fraction of austenite is calculated from the integrated intensities of the (200), (220), and (311) planes of fcc iron and the (200) and (211) planes of bcc iron.
[0063] Next, a method for producing a hot-rolled steel sheet and an electric resistance welded steel pipe according to an embodiment of the present invention will be described.
[0064] The hot-rolled steel sheet of the present invention is not particularly limited to the manufacturing conditions below, but for example, a steel material having the above-mentioned composition is heated to a heating temperature of 1100 ° C. or more and 1300 ° C. or less, and then subjected to hot rolling with an average cooling rate of 0.5 ° C. / s or more and 3.0 ° C. / s or less, a finish rolling end temperature of 750 ° C. or more and 850 ° C. or less, and a total rolling reduction in finish rolling of 45% or more and 75% or less, and then cooled with an average cooling rate of 5 ° C. / s or more and 40 ° C. / s or less at the center of the plate thickness from the finish rolling end temperature to the cooling stop temperature, a minimum cooling rate of 2 ° C. / s or more from the end of finish rolling to the stop of cooling, a cooling stop temperature of 400 ° C. or more and 650 ° C. or less, a continuous air-cooling time from the end of finish rolling to the stop of cooling: 15 s or less, a total air-cooling time: 50 s or less, and then wound into a coil.
[0065] The electric resistance welded steel pipe of the present invention is produced by forming the hot rolled steel sheet into a cylindrical shape by cold rolling, and then electric resistance welding the formed cylindrical shape.
[0066] In the following description of the manufacturing method, the temperature indicated in "°C" refers to the surface temperature of the steel material or steel plate (hot-rolled plate) unless otherwise specified. These surface temperatures can be measured with a radiation thermometer or the like. The temperature at the center of the thickness of the steel plate can be obtained by calculating the temperature distribution in the cross section of the steel plate by heat transfer analysis and correcting the result by the surface temperature of the steel plate. Furthermore, "hot-rolled steel plate" includes hot-rolled plate and hot-rolled steel strip.
[0067] In the present invention, the method of smelting the steel material (steel slab) is not particularly limited, and any of the known smelting methods such as converter, electric furnace, and vacuum melting furnace are suitable. The casting method is also not particularly limited, and the steel material is produced to the desired dimensions by a known casting method such as a continuous casting method. However, there is no problem even if an ingot casting-blooming rolling method is applied instead of the continuous casting method. The molten steel may further be subjected to secondary refining such as ladle refining.
[0068] The resulting steel material (steel slab) is then heated, hot rolled, cooled, and wound into a coil to form a hot-rolled steel sheet.
[0069] If the heating temperature is low, the deformation resistance of the rolled material increases, making rolling difficult. For this reason, the heating temperature is preferably 1100°C or higher. More preferably, it is 1120°C or higher. Even more preferably, it is 1130°C or higher. Most preferably, it is 1150°C or higher. On the other hand, if the heating temperature is high, the austenite grains become coarse, and fine austenite grains cannot be obtained in the subsequent rolling (rough rolling, finish rolling), and the average crystal grain size of the final product becomes large. For this reason, the heating temperature in the hot rolling process is preferably 1300°C or lower. More preferably, it is 1280°C or lower. Even more preferably, it is 1270°C or lower. Most preferably, it is 1250°C or lower.
[0070] In addition to the conventional method of producing a steel slab, once cooling it to room temperature and then reheating it, the present invention can also apply energy-saving direct rolling processes in which the slab is not cooled to room temperature, but is instead charged into a heating furnace as a hot slab, or is immediately rolled after a short period of heat retention.
[0071] If the average cooling rate from 900°C to 1100°C is small, the austenite will become coarse, and the average grain size of the final product will become large. For this reason, the average cooling rate from 900°C to 1100°C is preferably 0.5°C / s or more. More preferably, it is 0.8°C / s or more. Even more preferably, it is 0.9°C / s or more. Most preferably, it is 1.0°C / s or more. On the other hand, if the average cooling rate is large, the recrystallization of austenite will be insufficient, coarse austenite will remain, and the final product will have a steel structure in which coarse grains are mixed. As a result, the area ratio of grains having a grain size equal to or smaller than the average grain size will be low. For this reason, the average cooling rate from 900°C to 1100°C is preferably 3.0°C / s or less. More preferably, it is 2.5°C / s or less. Even more preferably, it is 2.4°C / s or less. Most preferably, it is 2.2°C / s or less.
[0072] If the finish rolling end temperature is low, the surface temperature of the steel sheet during finish rolling will be below the ferrite transformation start temperature, a large amount of worked ferrite will be generated, and ductility will decrease. Therefore, the finish rolling end temperature is preferably 750°C or higher. More preferably, it is 770°C or higher. Even more preferably, it is 780°C or higher. On the other hand, if the finish rolling end temperature is high, fine austenite grains will not be obtained, and the average crystal grain size will become large. Therefore, the finish rolling end temperature is preferably 850°C or lower. More preferably, it is 830°C or lower. Even more preferably, it is 820°C or lower.
[0073] If the total reduction in the finish rolling is low, sufficient processing strain cannot be introduced in the hot rolling process, and the average grain size of the final product becomes large. Therefore, the total reduction in the finish rolling is preferably 45% or more. The total reduction in the finish rolling is more preferably 50% or more. The total reduction in the finish rolling is even more preferably 52% or more. The total reduction in the finish rolling is most preferably 54% or more. On the other hand, if the total reduction in the finish rolling is high, the average grain size becomes small. In addition, the area ratio of grains having a grain size equal to or smaller than the average grain size becomes high. Therefore, the total reduction in the finish rolling is preferably 75% or less. More preferably, it is 70% or less. The total reduction in the finish rolling is even more preferably 68% or less. The total reduction in the finish rolling is most preferably 66% or less.
[0074] The total reduction in the above-mentioned finish rolling refers to the sum of the reductions in each rolling pass in the finish rolling.
[0075] From the viewpoint of ensuring the necessary rolling reduction rate and managing the steel sheet temperature, the finished sheet thickness is preferably 5 mm or more. The finished sheet thickness is more preferably 6 mm or more. Further preferably, the finished sheet thickness is 7 mm or more. Moreover, the finished sheet thickness is preferably 40 mm or less. The finished sheet thickness is more preferably 35 mm or less. Further preferably, the finished sheet thickness is 30 mm or less.
[0076] After the hot rolling, the hot-rolled sheet is cooled.
[0077] If the average cooling rate at the center of the plate thickness from the finish rolling end temperature to the cooling stop temperature is low, the structure will become coarse and the average crystal grain size of the final product will become large. Also, the bainite fraction will be low. Therefore, the average cooling rate is preferably 5°C / s or more. More preferably, it is 10°C / s or more. Even more preferably, it is 12°C / s or more. Most preferably, it is 15°C / s or more. On the other hand, if the average cooling rate at the center of the plate thickness is high, the martensite fraction will be high and the ductility will be reduced. Therefore, the average cooling rate is preferably 40°C / s or less. More preferably, it is 35°C / s or less. Even more preferably, it is 33°C / s or less. Most preferably, it is 30°C / s or less.
[0078] If the minimum cooling rate at the center of the plate thickness from the end of finish rolling to the end of cooling is low, the structure becomes coarse and the average crystal grain size becomes large. In addition, the area ratio of crystal grains having a grain size equal to or smaller than the average crystal grain size becomes low. In addition, the bainite fraction becomes low. Therefore, the minimum cooling rate is preferably 2°C / s or more. More preferably, it is 3°C / s or more. Even more preferably, it is 4°C / s or more. Most preferably, it is 5°C / s or more. Although there is no particular upper limit, the minimum cooling rate is preferably 15°C / s or less. More preferably, it is 12°C / s or less. Even more preferably, it is 10°C / s or less. Most preferably, it is 8°C / s or less. The minimum cooling rate is determined by dividing the time from the end of finish rolling to the end of cooling into sections of 3 seconds each, calculating the average cooling rate in each section, and taking the minimum value of these.
[0079] If the continuous air-cooling time from the end of finish rolling to the end of cooling is long, ferrite and bainite will grow excessively, the structure will become coarse, and the average crystal grain size of the final product will become large. In addition, the area ratio of crystal grains having a grain size equal to or smaller than the average crystal grain size will decrease. In addition, the bainite fraction may decrease. Therefore, the continuous air-cooling time is preferably 15 s or less. More preferably, it is 14 s or less. Even more preferably, it is 12 s or less. Most preferably, it is 11 s or less. The shorter the continuous air-cooling time, the better, but if it is less than 6 s, the effect of reducing the continuous air-cooling time will be small, and the equipment load will only increase, so the continuous air-cooling time is preferably 6 s or more. More preferably, it is 7 s or more. Even more preferably, it is 8 s or more. Between the end of finish rolling and the end of cooling, cooling is performed using air cooling and water cooling.
[0080] If the total air-cooling time from the end of finish rolling to the end of cooling is long, ferrite and bainite will grow excessively, the structure will become coarse, and the average crystal grain size of the final product will become large. In addition, the area ratio of crystal grains having a grain size equal to or smaller than the average crystal grain size will decrease. In addition, the bainite fraction may decrease. Therefore, the total air-cooling time is preferably 50 s or less. More preferably, it is 45 s or less. Even more preferably, it is 40 s or less. Most preferably, it is 38 s or less. The shorter the continuous air-cooling time, the better, but if it is less than 10 s, the effect of refining the grains with respect to the reduction in the total air-cooling time will be small, and the equipment load will only increase, so the total air-cooling time is preferably 10 s or more. More preferably, it is 12 s or more. Even more preferably, it is 15 s or more.
[0081] If the cooling stop temperature is low, the fraction of martensite increases and ductility decreases. Therefore, the cooling stop temperature is preferably 400°C or higher. More preferably, it is 420°C or higher. Even more preferably, it is 450°C or higher. Most preferably, it is 470°C or higher. On the other hand, if the cooling stop temperature is high, the fraction of bainite decreases. Therefore, the cooling stop temperature is preferably 650°C or lower. More preferably, it is 620°C or lower. Even more preferably, it is 600°C or lower. Most preferably, it is 580°C or lower.
[0082] In the electric resistance welded steel pipe of the present invention, in order to reduce the inclusion density in the welded portion, the width in the circumferential direction of the molten solidified portion of the welded portion (electric resistance welded portion) is preferably 1 μm or more over the entire thickness of the pipe. Also, the width in the circumferential direction of the molten solidified portion of the welded portion (electric resistance welded portion) is preferably 1000 μm or less over the entire thickness of the pipe.
[0083] The electric resistance welded steel pipe preferably has an outer diameter of 80 mm or more. The outer diameter is preferably 800 mm or less. The electric resistance welded steel pipe preferably has a wall thickness of 3 mm or more. The wall thickness is preferably 40 mm or less.
[0084] Here, the etching solution may be selected appropriately depending on the steel components and the type of steel pipe. FIG. 4 shows a schematic diagram of the circumferential cross section of the electric resistance welded part of an electric resistance welded steel pipe. The molten solidified part 15 can be visually recognized as a region having a structure form and contrast different from the base metal part 13 and the heat-affected part 14 in FIG. 4, as shown in the schematic diagram of the cross section after corrosion in FIG. 4. For example, the molten solidified part 15 of an electric resistance welded steel pipe of carbon steel and low alloy steel can be identified as a region observed as white under an optical microscope in the cross section corroded with nital. Also, the molten solidified part 15 of a UOE steel pipe of carbon steel and low alloy steel can be identified as a region containing a cellular or dendritic solidified structure under an optical microscope in the cross section corroded with nital. EXAMPLES
[0085] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.
[0086] Molten steel having the chemical composition shown in Table 1 was produced into a slab (steel material). The obtained slab was subjected to a hot rolling process and a cooling process under the conditions shown in Table 2, and further to a coiling process, to produce a hot-rolled steel sheet having a finished thickness (mm) shown in Table 2.
[0087] After the coiling process, the hot-rolled steel sheet was rolled into a cylindrical round steel pipe, and the butt joint was electric resistance welded. The round steel pipe was then reduced in diameter by rolls arranged above, below, left and right of the round steel pipe to obtain electric resistance welded steel pipes with the outer diameter (mm) and wall thickness (mm) shown in Table 4.
[0088] Test pieces were taken from the obtained hot-rolled steel sheets and electric resistance welded steel pipes shown in Tables 3 and 4, respectively, and the following C-type flattening tests, flattening tests, average crystal grain size measurements, measurements of the area ratio of crystal grains with grain sizes smaller than the average crystal grain size, fine grain connectivity measurements, and structure observations were performed. The various test pieces were taken from the center of the plate thickness at the center in the width direction for the hot-rolled steel sheets, and from the center of the plate thickness of the base material part 90° away from the electric resistance weld in the circumferential direction of the pipe for the electric resistance welded steel pipes.
[0089] [C-type flattening test] For the C-type flattening test, a plate material (test piece) with a full thickness, width of 50 × t (t: plate thickness), and length of 100 mm was taken from the hot-rolled steel plate so that the longitudinal direction of the test piece was the plate width direction of the hot-rolled steel plate, and then this was made into a C-type test piece by the press-bending method described in JIS Z 2248 (2006), and then the test was performed according to the method described in JIS G 3441 (2021). In the press-bending, the inner radius of the tip of the pressing metal fitting was 9 × t. The initial curvature radius r of the bent outer surface of the flattened test piece was obtained by adding the plate thickness to the inner radius of the tip of the pressing metal fitting in the press-bending, as shown in formula (4). r = 10 × t (4) When a crack of 0.50 mm or more in length was observed on the outer surface of the bent piece in the tightly attached state, it was judged that there was a crack, and when no crack was observed on the outer surface of the bent piece, it was judged that there was no crack.
[0090] [Flattening test] The flattening test was performed by taking 100 mm long sliced test pieces from an electric-resistance welded steel pipe including an electric-resistance weld from the axial direction of the pipe, using the method described in JIS G 3441 (2021). However, the test specimen was placed so that the welded part faced the compression direction, as shown in Figure 3. The initial radius of curvature r of the bent outer surface of the flattened test specimen was set to half the outer diameter of the electric resistance welded steel pipe. If a crack of 0.50 mm or more in length had occurred on the outer surface of the pipe in a tightly sealed state, it was judged to have cracks, and if no cracks had occurred on the outer surface of the pipe, it was judged to have no cracks.
[0091] [Average grain size measurement] The average grain size was measured by taking test pieces for measurement so that the measurement surface was a cross section parallel to both the rolling direction and the plate thickness direction of the hot-rolled steel sheet, and a cross section parallel to both the pipe axis direction and the wall thickness direction of the electric resistance welded steel pipe, mirror-polishing them, and then using the SEM / EBSD method. The grain size was measured by determining the orientation difference between adjacent grains, and the boundary with an orientation difference of 15° or more was considered as a grain boundary, and the area surrounded by an orientation difference of 15° or more was considered as one grain. The arithmetic average of the grain size was calculated from the obtained grain boundaries, and the average grain size was obtained. The acceleration voltage was 15 kV, the measurement area was 500 μm × 500 μm, the measurement step size was 0.5 μm, and the measured values of 5 fields or more were averaged. Based on the obtained EBSD data, the grain boundary and grain size distribution was obtained by using the crystal orientation analysis software OIM Analysis (trademark), with the boundary with an orientation difference of 15° or more being considered as a grain boundary (high angle grain boundary). The grain size and average grain size were calculated as the diameter of a circle with an area equal to the total measured area divided by the number of grains (equivalent circle diameter). In calculating the average grain size, grains with a grain size of 1.0 μm or less were excluded as measurement noise.
[0092] [Measurement of area ratio of crystal grains having a grain size equal to or smaller than the average crystal grain size] It was calculated from the average crystal grain size and the grain size distribution obtained above. For each crystal grain with a grain size equal to or smaller than the average crystal grain size, the area was calculated from its equivalent circle diameter, the total area of the crystal grains with a grain size equal to or smaller than the average crystal grain size was calculated, and this was divided by the area of the measurement region to obtain the area ratio. In calculating the area ratio of crystal grains with a grain size equal to or smaller than the average crystal grain size, crystal grains with a grain size of 1.0 μm or less were excluded as measurement noise.
[0093] [Fine grain connectivity] The fine grain connectivity was calculated by calculating the total length of high-angle boundaries in the region excluding grains with a grain size equal to or larger than the average grain size, and the total length of high-angle boundaries in all grains, and then calculating the ratio between them. However, the total length of high-angle boundaries in grains with a grain size smaller than the average grain size, which is written in the numerator on the right side of the above-mentioned equation (3), does not include the length of high-angle boundaries between grains with a grain size smaller than the average grain size and grains with a grain size equal to or larger than the average grain size. In addition, in calculating the fine grain connectivity, crystal grains with a crystal grain size of 1.0 μm or less were excluded as measurement noise.
[0094] [Textural Observation] The test pieces for microstructural observation were taken so that the observation surface was a cross section parallel to both the rolling direction and the plate thickness direction of the hot-rolled steel sheet, and a cross section parallel to both the pipe axis direction and the wall thickness direction of the electric resistance welded steel pipe, respectively, and were prepared by mirror polishing and etching with nital. The microstructural observation was performed using an optical microscope (magnification: 1000 times) or a scanning electron microscope (SEM, magnification: 1000 times) to observe and photograph the microstructure at the center of the plate thickness of the hot-rolled steel sheet and the center of the wall thickness of the electric resistance welded steel pipe. The SEM observation was performed at an accelerating voltage of 15 kV. The area ratios of bainite and the remainder (ferrite, pearlite, martensite, austenite) were obtained from the obtained optical microscope images and SEM images. The area ratios of each microstructure were calculated as the average value of the values obtained in five or more visual fields. Here, the area ratios obtained by microstructural observation were taken as the volume ratios of each microstructure.
[0095] From the above, the determination of ferrite, pearlite, and martensite is carried out by the method described in the embodiment.
[0096] The volume fraction of austenite was measured by X-ray diffraction. The test pieces for the measurements at the center of thickness of the hot-rolled steel plate and the center of thickness of the electric resistance welded steel pipe were prepared by grinding so that the diffraction surface was at the center of thickness of the hot-rolled steel plate and the center of thickness of the electric resistance welded steel pipe, respectively, and then chemically polishing to remove the surface-worked layer. The measurements used Mo Kα radiation, and the volume fraction of austenite was calculated from the integrated intensity of the (200), (220), and (311) planes of fcc iron and the (200) and (211) planes of bcc iron.
[0097] The results obtained are shown in Tables 3 and 4.
[0098] [Table 1]
[0099] [Table 2]
[0100] [Table 3]
[0101] [Table 4]
[0102] In Tables 3 and 4, the hot-rolled steel sheets and electric resistance welded steel pipes Nos. 1, 4, 6, 8, 9, and 11 to 24 are examples of the present invention, and the hot-rolled steel sheets and electric resistance welded steel pipes Nos. 2, 3, 5, 7, and 10 are comparative examples.
[0103] In the C-type flattening test, none of the hot-rolled steel sheets of the present invention showed cracks of 0.50 mm or more in length until they reached a tight contact state, and the (normalized load / normalized displacement) value was 100 MPa or more when the normalized displacement was in the range of 0.20 to 0.30.
[0104] In the flattening test, none of the electric welded steel pipes of the present invention showed cracks of 0.50 mm or more in length until they reached a tightly sealed state, and the (normalized load / normalized displacement) value was 100 MPa or more when the normalized displacement was in the range of 0.20 to 0.30. [Explanation of symbols]
[0105] 1. Curve showing the change in normalized load with normalized displacement 2 Elastic region 3 Plastic region 4. Cracks or adhesion 5A Test Piece 5 C-shaped flat test piece (flat test piece) 6 flat plate 7 Compression Direction 8 Flat test piece 9 Electric resistance welded section 10. Electric resistance welded steel pipe center 11 flat plate 12 Compression direction 13 Base metal part 14 Heat-affected zone 15 Melted and solidified part 100 Initial length of test piece L 101 Initial thickness of test piece t 102 Rolling direction of hot-rolled steel sheet
Claims
1. The composition, in mass%, is C: 0.020% or more and 0.200% or less, Si: 0.50% or less, Mn: 0.30% or more and 2.00% or less, P: 0.050% or less, S: 0.0200% or less, Al: 0.005% or more and 0.100% or less, N: 0.0100% or less; Or even more so: Nb: 0.080% or less, V: 0.080% or less, Ti: 0.080% or less, Cu: 0.50% or less, Ni: 0.50% or less, Cr: 0.50% or less, Mo: 0.50% or less, Ca: 0.0050% or less, B: 0.0050% or less, Mg: 0.020% or less, Zr: 0.020% or less, REM: 0.020% or less, Sn: 0.100% or less, one or more of the following are included; The balance is Fe and unavoidable impurities, In the C-type flattening test, a test piece made by bending a steel plate into a U-shape is clamped between two flat plates. No cracks having a length of 0.50 mm or more are generated until the inner surfaces of the bent test pieces come into contact with each other, and When the normalized displacement calculated by the following formula (2) is in the range of 0.20 to 0.30, the normalized load / normalized displacement calculated by the following formula (1) is 100 MPa or more, The steel structure at the center of the plate thickness is The average grain size of the grains in the region surrounded by the high-angle grain boundaries is 15.0 μm or less, The crystal grains having a grain size equal to or smaller than the average crystal grain size account for 10% or more and 50% or less of all crystal grains, The fine grain connectivity calculated by the following formula (3) is 0.05 or more and 0.50 or less, and The volume fraction of bainite is 10% or more, The total volume fraction of ferrite and bainite is 80% or more, The balance is one or more selected from pearlite, martensite and austenite, the total of which is 20% or less by volume. Hot rolled steel plate. (Normalized load (MPa)) = (P / L) x (r / t 2 ) x (1 - ((x 0 - x) / 2r) 2 ) 1 / 2 ... (1) (Normalized displacement)=(x 0 −x) / 2r (2) Where: P: Load (N) L: Initial length of the flattened test piece (mm) r: initial radius of curvature of the outer surface of the bent flattened test piece (mm) t: initial thickness of flattened test piece (mm) x 0 : Initial distance between the two plates (mm) x: Distance between two plates (mm) (Fine grain connectivity)=(total length of high angle grain boundaries in grains having a grain size smaller than the average grain size) / (total length of high angle grain boundaries) (3) However, the numerator on the right side of equation (3) does not include the length of the high-angle grain boundary between crystal grains smaller than the average crystal grain size and crystal grains larger than or equal to the average crystal grain size.
2. An electric resistance welded steel pipe having a base material portion and an electric resistance welded portion, The composition of the base material is, in mass%, C: 0.020% or more and 0.200% or less, Si: 0.50% or less, Mn: 0.30% or more and 2.00% or less, P: 0.050% or less, S: 0.0200% or less, Al: 0.005% or more and 0.100% or less, N: 0.0100% or less; Or even more so: Nb: 0.080% or less, V: 0.080% or less, Ti: 0.080% or less, Cu: 0.50% or less, Ni: 0.50% or less, Cr: 0.50% or less, Mo: 0.50% or less, Ca: 0.0050% or less, B: 0.0050% or less, Mg: 0.020% or less, Zr: 0.020% or less, REM: 0.020% or less, Sn: 0.100% or less, one or more of the following are included; The balance is Fe and unavoidable impurities, In a flattening test, a flattened test piece taken from an electric resistance welded steel pipe is clamped between two flat plates. No cracks having a length of 0.50 mm or more are generated until the inner surfaces of the flattened test pieces come into contact with each other, and When the normalized displacement calculated by the following formula (2) is in the range of 0.20 to 0.30, the normalized load / normalized displacement calculated by the following formula (1) is 100 MPa or more, The steel structure at the center of the thickness of the base material portion is The average grain size of the grains in the region surrounded by the high-angle grain boundaries is 15.0 μm or less, The crystal grains having a grain size equal to or smaller than the average crystal grain size account for 10% or more and 50% or less of all crystal grains, The fine grain connectivity calculated by the following formula (3) is 0.05 or more and 0.50 or less, and The volume fraction of bainite is 10% or more, The total volume fraction of ferrite and bainite is 80% or more, The balance is one or more selected from pearlite, martensite and austenite, the total of which is 20% or less by volume. ERW steel pipe. (Normalized load (MPa)) = (P / L) x (r / t 2 ) x (1 - ((x 0 - x) / 2r) 2 ) 1 / 2 ... (1) (Normalized displacement)=(x 0 −x) / 2r (2) Where: P: Load (N) L: Initial length of the flattened test piece in the axial direction (mm) r: initial radius of curvature of the outer surface of the bent flattened test piece (mm) t: initial thickness of flattened test piece (mm) x 0 : Initial distance between the two plates (mm) x: Distance between two plates (mm) (Fine grain connectivity)=(total length of high angle grain boundaries in grains having a grain size smaller than the average grain size) / (total length of high angle grain boundaries) (3) However, the numerator on the right side of equation (3) does not include the length of the high-angle grain boundary between crystal grains smaller than the average crystal grain size and crystal grains larger than or equal to the average crystal grain size.
Citation Information
Patent Citations
Resistance welded steel tube for heat treatment, and its manufacturing method
JP2008208417A
HEAT TREATED STEEL MATERIAL, ULTRA-HIGH-STRENGTH MOLDED PRODUCT EXCELLENT IN DURABILITY AND PRODUCTION METHOD THEREOF
JP2018506642A
Electric resistance welded steel pipe, its manufacturing method and automotive structural member
JP6954504B1
Electric resistance welded steel pipe and method for producing same, and line pipe and building structure
WO2021085036A1